2009
DOI: 10.1128/jb.00672-09
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the Escherichia coli guaB Promoter by Upstream-Bound Cyclic AMP Receptor Protein

Abstract: The Escherichia coli guaB promoter (P guaB ) is responsible for directing transcription of the guaB and guaA genes, which specify the biosynthesis of the nucleotide GMP. P guaB is subject to growth rate-dependent control (GRDC) and possesses an UP element that is required for this regulation. In addition, P guaB contains a discriminator, three binding sites for the nucleoid-associated protein FIS, and putative binding sites for the regulatory proteins DnaA, PurR, and cyclic AMP receptor protein (CRP). Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…In many cases, the cAMP-CRP complex binding site is positioned at a relatively long distance from the transcription start site (38). Downregulation of the guaB promoter by the cAMP-CRP complex has been reported at position Ϫ117.5 (14). In this study, the results shown in Fig.…”
Section: Discussionsupporting
confidence: 62%
“…In many cases, the cAMP-CRP complex binding site is positioned at a relatively long distance from the transcription start site (38). Downregulation of the guaB promoter by the cAMP-CRP complex has been reported at position Ϫ117.5 (14). In this study, the results shown in Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Often, numerous purine nucleotide biosynthesis genes are found in the same operons, allowing them to be controlled by a single, regulatory mechanism (34)(35)(36). Regulators for purine nucleotide biosynthesis and salvage pathways are abundant; regulatory promoter-binding proteins (33,34) and riboswitches (4,43) are utilized for many of these genes in most other bacteria. By comparison, the purine synthesis genes found in H. pylori are spread throughout the genome (44) without any apparent order or regulation.…”
Section: Fig 12mentioning
confidence: 99%
“…Genes comprising either pathway often are found in operons (34)(35)(36) and are often regulated by the same regulatory promoterbinding proteins (33,34) or riboswitches (4,43), generating feedback loops that allow the organism to alternate between the two synthesis pathways while maintaining adequate purine nucleotide pools. Additionally, the allosteric regulation of nucleotide pools has also been shown in key enzymes in both purine (60,61) and pyrimidine (59) nucleotide biosynthesis, indicating enzyme activity also may add an additional means of regulation.…”
mentioning
confidence: 99%
“…These functions include energy transfer (ATP and GTP) and cell signaling [cyclic AMP (cAMP), bis-(3=-5=)-cyclic di-GMP (c-di-GMP), and guanosine tetraphosphate (ppGpp)] (11,17). The secondary signal molecule, cAMP, is synthesized from AMP by adenylate cyclase, which is encoded by cyaA (21) and is broken down to 5=-AMP by cAMP phosphodiesterase, encoded by cpdA (22). The receptor for cAMP is the cAMP receptor protein, encoded by crp (21).…”
mentioning
confidence: 99%